Hubungan Tingkat Risiko Dengan Health Beliefs Tentang Perilaku Pencegahan Diabetes Melitus Tipe 2 Pada Mahasiswa STIKes Panti Rapih Yogyakarta - Jekau, Beatrix Vionita; Subiyanto, Paulus; Kristanti, Fittriya (I Care Jurnal Keperawatan STIKes Panti Rapih, 2025)
Background: Type 2 diabetes mellitus (T2DM) is a global health problem whose prevalence is increasing and is characterized by decreased insulin function and/or relative insulin deficiency. In Indonesia, the prevalence of T2DM is increasing and is ranked fourth in the number of diabetes sufferers worldwide at 20.4 million or 8.4%. This disease can occur at productive ages < 35 years. STIKes Panti Rapih Yogyakarta students are included in the population that is vulnerable to risk with a prevalence of 34.92%. Objective: This study aims to determine the relationship between risk level and health beliefs regarding T2DM prevention behavior among STIKes Panti Rapih students Method: This research is a quantitative survey type research with a cross sectional design. The population in this study was 573 STIKes Panti students. By using random sampling techniques, a sample of 260 people was obtained. Results: Based on the research results, there were 142 students, 54.65%) who had a low risk of experiencing T2DM and 179 students (68.8%) had high health beliefs. The results of the statistical test of the relationship between risk level and health beliefs regarding behavior to prevent type 2 DM among students at the Yogyakarta neat and tidy institutions showed a p-value of 0.0095. Conclusion: There is no relationship between the risk level of T2DM and health beliefs because based on education level, age, and disease history, the majority have a low risk of experiencing Type 2 DM. So further research is needed on the relationship between risk level and T2DM prevention behavior among STIKes Panti Rapih students. Keywords: Risk level, Health Beliefs in students, Type 2 DM